Sustainability of poverty alleviation: a case of Thogoaneng and Maratapelo villages in Limpopo Province, South Africa - Mashiane, Matsimela Joas (University of Limpopo (Turfloop Campus), 2008)
Refer to document
Thesis (M.Dev.) --University of Limpopo, 2008
Keywords: Poverty alleviation projects; 362.5968; Poverty; Rural poor -- South Africa